Fabrication of Eddy Current Probe for SS 304 tube inspection / Muhamad Hazly Muhamad Nordin - Muhamad Nordin, Muhamad Hazly (2004)
The final year student of UiTM Mechanical Engineering under supervision of Prof. Madya Noraini Wahab has carried out this project of "Fabrication of Eddy Current Probe For SS 304 Tube Inspection". The important part about this project is to study some basic theory that involve in eddy current testing. As we know, eddy current testing is one of the major Non-Destructive methods for tube testing. It used a localized electrical field that is introduced into a conductive test specimen by electromagnetic induction. Virtually all-conductive materials can be examined for flaws, metallurgical conditions, thinning and conductivity. The technique is quick, versatile, and sensitive, can be no contacting and is easily adaptable to automation and in site examination. The main purpose of this final year project is to fabricate eddy current probe using parameters obtained from governing equation by choosing the best eddy current signal with the respect to number of coil winding that can be used for testing defects in SS 304 tube.